Kekristenan dan Spiritualitas Online: Cybertheology sebagai Sumbangsih Berteologi di Indonesia - Sopacoly, Mick Mordekhai; Lattu, Izak Y.M. (Faculty of Theology Duta Wacana Christian University, 2020)
Abstract The mobilization of information, technology, and social change marked by the presence of cyberspace not only affects the way people think in building relationships with others and themselves but also the process of developing faith and spirituality. Using the methods of qualitative research, literature study, and Focus Group Discussion (FGD), this research finds that in the context of the COVID-19 pandemic, Christian religious patterns are changing drastically, driving all churches to move to virtual reality. The Christian notion of spirituality is also being transformed so that the experience with God is believed to occur not only in the physical space of the church but also in virtual reality. â€œClickactivismâ€ forms a new faith community determined by click and spiritual experiences which strength lies in the imagination of communities and individuals. This study concludes that cybertheology is an important contribution in helping Indonesian Christians to have a strong spiritualityabout God who cannot be confined within time and space. Abstrak Arus mobilisasi informasi, teknologi, dan perubahan sosial yang ditandai dengan adanya ruang cyber (cyberspace) ternyata tidak hanya mempengaruhi cara berpikir manusia dalam membangun relasi dengan sesama dan diri sendiri tetapi juga proses pengembangan iman dan spiritualitasnya. Metode yang digunakan ialah penelitian kualitatif, studi literatur, dan Focus Group Discussion (FGD). Hasil penelitian menemukan bahwa dalam konteks pandemi COVID-19, pola beragama Kristen berubah secara drastis sehingga memaksa semua gereja untuk pindah ke realitas virtual. Pemahaman kekristenan tentang spiritualitas juga bertransformasi sehingga pengalaman dengan Tuhan diyakini tidak terbatas dalam ruang fisik gereja tetapi juga dalam realitas virtual. â€œAktivitas klikâ€ membentuk sebuah komunitas iman yang baru, yang ditentukan oleh klik dan pengalaman spiritual yang kekuatannya terletak pada imajinasi komunitas dan individu. Karena itu, studi ini menyimpulkan bahwa teologi cyber menjadi kontribusi penting untuk membantu kekristenan di Indonesia untuk berspiritualitas mengenai Tuhan yang tidak dapat dikurung dalam ruang dan waktu.